The glymphatic system as a therapeutic target: TMS-induced modulation in older adults - Sundman, Mark H.; Liu, Yilin; Chen, Nan-kuei; Chou, Ying-hui (Frontiers in Aging Neuroscience, 2025)
While repetitive transcranial magnetic stimulation (rTMS) is a promising neuromodulatory intervention for cognitive impairment, its effects on the glymphatic system remain unexplored in clinical populations. Deficient glymphatic clearance has emerged as a central feature of neurodegenerative disease, which can now be assessed with specialized diffusion magnetic resonance imaging techniques. This study examines changes in the diffusion tensor imaging analysis along the perivascular space (DTI-ALPS) index following theta-burst stimulation (TBS) in older adults with mild cognitive impairment (MCI). DTI-ALPS is an MRI-based measure that reflects the efficiency of the brain’s glymphatic waste removal system, as it quantifies how easily water molecules move along the perivascular spaces where waste is cleared. Participants underwent ten consecutive days of continuous TBS, intermittent TBS, and sham TBS, with DTI-ALPS measurements acquired before and after each intervention. Our sham-controlled findings reveal the capacity for TBS interventions to modulate glymphatic function and highlight a significant APOE ε4 effect. Specifically, ε4 carriers exhibited a lower baseline DTI-ALPS index (p < 0.05, Cohen’s d = 0.610), suggesting reduced glymphatic function, which was selectively responsive to TBS interventions (p < 0.005, Cohen’s d = 1.71). Further, within this subgroup, TBS-induced increases in glymphatic function correlated with memory improvements (r = 0.42–0.46, p < 0.05). These results provide novel evidence that TBS can modulate glymphatic function in humans and raise interesting questions about the relevance of APOE status. Further research is needed to elucidate the mechanisms underlying these effects and their therapeutic implications.